Pengaruh Tagline Instagram dan E-Wom terhadap Pembentukan Brand Awareness dan Kepercayaan Pelanggan Provider Digital By.U Tahun 2024 - Nadine Shafa Nabila; Mahfud Anshori (Jurnal Komunikasi Massa, 2024)
In current technology age, By.U provider's electronic word-of-mouth (EWOM) and tagline management are expanding quickly. By.U’s unique, creative, and memorable tagline is a distinctive feature of By.U’s ability to strengthen its brand positioning in the minds of its customers. It’s brand awareness is also higher in its customers’ minds because of its ability to manage EWOM in a more proactive and structured manner. In 2024, this research intends to examine how EWOM and the Instagram slogan #CumaKamuYangBisa @byu.id will affect the development of brand awareness. Two independent variables make up this study: electronic word of mouth (X2) with intensity, valence of opinion, and substance; and tagline (X1) with familiarity, distinction, and message/value. Concerning the factors influenced by this research, brand awareness (Y) is related to brand memory, brand purchase, brand recognition, and brand consumption. 300 people responded to the study, which employs quantitative approaches and sampling strategies based on Hair Theory. Using SPSS 29, the researchers run statistical descriptive, validity, reliability, classical assumption, and hypothesis tests. It may be concluded from the double linear regression result Y = 8.593 + 0.101X1 + 0.989X2 that tagline (X1) and EWOM (X2) have favorable effects on brand awareness (Y). The partial test results for the tagline variable (2.402) and the variable EWom (18.837) show that both variables have values higher than the value of the tables (1.967 with a significance value of 5%). The determined coefficient has a 64.3% impact on the brand awareness by U, the remainder of which is impacted by other variables. Both independent variables have a substantial effect on the dependent variable.